Pemberdayaan Petani Muda melalui Sekolah Alternatif Pertanian Biji Kopi Borneo di Banjarbaru - Dewi, Tiara Kusuma; Hidayah, Sri (Huma: Jurnal Sosiologi, 2025)
The declining interest in becoming farmers, especially among the younger generation or successors, poses a challenge in how to achieve farmer regeneration for future food security. This research aims to understand and analyse in depth using the community empowerment theory, namely ACTORS (Authority, Confidence and Competence, Trust, Opportunities, Responsibilities, Support) regarding the forms of training, as well as the outcomes produced both in terms of capacity and the social-humanistic aspect of the Biji Kopi Borneo alternative agricultural school in Banjarbaru City. This research uses a qualitative research approach with a phenomenological research type. The data collection techniques used were observation, interviews, and documentation. The research results using the ACTORS framework prove that the Borneo Coffee Bean training comprehensively with the upstream to downstream concept meets every input of the ACTORS framework. Thus, it can effectively and efficiently enhance the capacity, skills, self-confidence, recognition, and independence of each participant. Providing moral and material support can change the negative stigma associated with the farming profession in the participants. Practicing directly the processing techniques from the planting process to the post-harvest process, to enhance innovation and creativity. Based on the ACTORS analysis results of the training, it creates independent and adaptive young farmers. They contribute to the agricultural sector towards the development of their hometown, community service, and fostering an entrepreneurial spirit among the youth. This research provides a reference for future studies, particularly highlighting the topic of alternative agricultural schools as a new social movement based on empowerment. Further research is recommended to highlight empowerment programs in realising farmer regeneration